The community profiles of symbiotic bacteria at the different life stages of coral Dipsastraea favus - Xu, Jianjun; Chai, Guangjun; Xiao, Yilin; Xie, Ziqiang; Yang, Xiaodong; Liao, Baolin; Xiao, Baohua; Li, Zhiyong (Frontiers in Marine Science, 2023)
Corals live in a symbiotic relationship with various bacteria. The establishment of coral microbial community in early developmental stages is fundamental to coral fitness, health and survival, but the bacterial communities across the life history of corals is still poorly characterized, particularly the stage-specific bacteria and their possible ecological roles. In this study, the diversity of bacteria in the eggs, larvae and adults of coral Dipsastraea favus were investigated by sequencing 16S ribosomal RNA gene. As a result, no bacteria were detected in the eggs of D. favus. Bacteria were observed only in the planula larvae and adults. The bacterial diversity in the planula larvae was particularly higher than that in the adult D. favus. The dynamic bacterial community profiles indicate that D. favus can acquire specific symbiotic bacteria from the environment by horizontal transmission. In particular, life stage-related bacteria, e.g. Oceanospirillaceae and Kordia in larvae, Kiloniellales and Prosthecochloris in adult D. favus may play important roles in the coral development. The variant community of bacteria at the different life stages of D. favus is helpful for our understanding of the coral-bacteria symbioses.